Altered functional connectivity in blepharospasm/orofacial dystonia. Issue 1 (18th December 2017) - Jochim, Angela; Li, Yong; Gora‐Stahlberg, Gina; Mantel, Tobias; Berndt, Maria; Castrop, Florian; Dresel, Christian; Haslinger, Bernhard
Abstract: Introduction: Blepharospasm is characterized by involuntary eyelid spasms. It can be associated with perioral dystonia (Meige's syndrome or orofacial dystonia). We aimed at studying resting‐state functional brain connectivity in these patients and its potential modulation by therapeutic botulinum toxin injections. Methods: We performed resting‐state functional MRI and a region of interest‐based analysis of functional connectivity in 13 patients with blepharospasm/Meige's syndrome in comparison to 13 healthy controls. Patients were studied before and 4 weeks after botulinum toxin treatment. Simultaneous facial electromyography was applied to control for involuntary facial movements. Results: Before botulinum toxin treatment, patients showed reduced functional connectivity between caudate and primary sensorimotor, somatosensory association and visual cortices as well as between putamen and parietal association cortex. Cerebellar areas displayed decreased functional connectivity to somatosensory and visual association cortices. On the cortical level, connectivity was reduced between the cingulate cortex and the primary sensorimotor/premotor and parietal association cortex, between premotor areas and the primary somatosensory cortices, and between the postcentral gyrus and temporoparietal, secondary somatosensory, cingular, and cerebellar regions. Botulinum toxin treatment modulated functional connectivity, especially between cerebellum and visual cortices. Conclusions: Patients with blepharospasm/Meige's syndrome show altered functional connectivity at rest in widespread brain regions including basal ganglia, cerebellar, primary/secondary sensorimotor, and visual areas. Functionally, this may reflect a predisposition for defective movement inhibition and sensorimotor integration. Botulinum toxin treatment could modulate brain connectivity in blepharospasm by altering visual and sensory input. Abstract : We analyzed functional brain connectivity in blepharospasm/mild Meige's syndrome using resting state fMRI in combination with online electromyographic control of facial muscle activity. Our results show a widespread FC alteration within in brain networks including basal ganglia, sensorimotor and visual cortex, cingulum, and cerebellum, which can be modulated by peripheral muscle denervation with botulinum toxin.